KONFLIK TANAH ULAYAT ANTARA KAMANAKAN MALAKOK DENGAN NINIAK MAMAK SUKU TOBO DI NAGARI PADANG LAWEH KECAMATAN KOTO VII KABUPATEN SIJUNJUNG - Ningsih, Welda; Anggreta, Dian Kurnia; Fitlayeni, Rinel (Pendidikan Sosiologi, 2013)
This paper describes the background of communal indigenous land conflicts between kamanakan  malakok  with  niniak  mamak  Tobo  tribe,  in  Nagari  Koto  Padang  District  VII Laweh Sijunjung district. Conflict begins with the presence of communal land area of ± 2500 m²  (1/4hektar)  located  in  Ganting  (SMP  8  Nagari  Padang  Simpang  Laweh)  Jorong  Koto Padang Laweh which is belongs  niniak mamak  Tobo tribe of the land has not been tilled by niniak mamak and still empty. However kamanakan malakok fence and mengarap without the permission and knowledge of niniak mamak  triggering conflict. The research problem is how the background to the conflict  and resolution of conflicts between  kamanakan malakok  with niniak mamak  Tobo tribe in Nagari Padang Laweh.  The purpose of this study describes the background to the conflict and the resolution of conflict between  kamanakan malakok  with niniak mamak Tobo tribe in Nagari Koto Padang Laweh District VII.  In this study, the author uses the theory of Lewis Coser, to avoid conflicts from the sharper the necessary safety valve.The approach used in this study is a qualitative approach  with descriptive type to provide a detailed  picture  of  the  reality  under  study.  Data  was  collected  through  observation  and interviews.  Informants  were taken by sampling porposive.  Based on the results of research conducted,  communal land conflicts caused by  malakok  nephew who worked and fencing of communal  land  without  the  permission  and  knowledge  of  the  Tobo  tribe  niniak  mamakresulting land conflict issues.  While the form of conflict resolution through deliberation and consensus between the two sides, conflict is not resolved by the prince of the tribe  resulting in the issue resolved through official organizations, the wali nagari the prince of the tribe and last through the police, after receiving the decision of the police, found both parties and reach an agreement by dividing 2 lands which are written above the letter of agreement, signed byboth parties.